2016
DOI: 10.6028/jres.121.005
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Gas Phase Enthalpies of Formation for Hydrogen-Oxygen (HxOy) Species

Abstract: We have compiled gas phase enthalpies of formation for nine hydrogen-oxygen species (HxOy) and selected recommended values for H, O, OH, H2O, HO2, H2O2, O3, HO3, and H2O3. The compilation consists of values derived from experimental measurements, quantum chemical calculations, and prior evaluations. This work updates the recommended values in the NIST-JANAF (1985) and Gurvich et al. (1989) thermochemical tables for seven species. For two species, HO3 and H2O3 (important in atmospheric chemistry) and not found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 129 publications
1
2
0
Order By: Relevance
“…The only member of this family sufficiently well-known to be included in the Active Thermochemical Tables or to feature in a recent review is trioxidane or dihydrogen trioxide, HOOOH, the trans conformer of which has a formation enthalpy, Δ f H (0 K), of −81.40 ± 0.78 kJ mol –1 ; this is in good agreement with the W3X-L value of −82.1 kJ mol –1 .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The only member of this family sufficiently well-known to be included in the Active Thermochemical Tables or to feature in a recent review is trioxidane or dihydrogen trioxide, HOOOH, the trans conformer of which has a formation enthalpy, Δ f H (0 K), of −81.40 ± 0.78 kJ mol –1 ; this is in good agreement with the W3X-L value of −82.1 kJ mol –1 .…”
Section: Resultssupporting
confidence: 60%
“…Hydrotrioxides. The only member of this family sufficiently well-known to be included in the Active Thermochemical Tables 40 or to feature in a recent review 63 A recent communication considered the reaction between methyl peroxy and hydroxyl radicals, from which an enthalpy of formation for methyl hydrotrioxide of −65.3 ± 3.5 kJ mol −1 can be derived. 64 Earlier, Jungkamp and Seinfeld 65 had derived a value for Δ f H(298.15 K) of −94 kJ mol −1 from G2M(RCC) calculations.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In other studies, the formation of the hydrotrioxyl radical (HO 3 ) was also found to react with O 2 , but due to the low-calculated HO 3 abundance in the troposphere, this radical may also be a minor pathway to HO 2 . Although the reaction HO 3 +NO to form HO 2 +NO 2 is exothermic, it, to our knowledge, has not been tested (Murray et al, 2008;Le Picard et al, 2010;Burgess Jr, 2016). Therefore, the role of O 2 reactions with excited-state intermediates to form HO 2 in the presence of NO remains an open question.…”
Section: Ho 2 Versus Nomentioning
confidence: 99%
“…The recommended value in the ATcT database for the enthalpy of formation of the HO 2 radical is Δ f H 0 0K (HO 2 ) = 15.12 ± 0.15 kJ mol −1 , 7 and NIST suggests a value of 15.21 ± 0.35 kJ mol −1 . 8 Ganyecz et al used the composite theoretical/thermochemical network approach to find the enthalpies of formation of 14.85 ± 0.22 kJ mol −1 for the neutral HO 2 radical and of 1110.56 ± 0.40 kJ mol −1 for the cation HO 2 + , which yields an AIE of the HO 2 radical at 11.356 ± 0.005 eV. 9 Our directly measured AIE value, 11.359 ± 0.003 eV, corroborates the network data of Ganyecz et al 9 within the error bars and could be used to further refine it.…”
Section: Resultsmentioning
confidence: 99%